Development of the home environment risk rating scale and investigation of the psychometric properties in the elderly and adult individuals. - Akyurek, Gokcen; Bilgin, Nurten; Kocademir, Fatma Nur; Aslan, Sultan; Turk, Ayşe Betul (Journal of Public Health: From Theory to Practice (2198-1833), 2024)
Aim: To reduce home accidents, which is one of the critical public health problems, it is necessary to evaluate the home environment first. The aim of this study was to develop the Home Environment Risk Rating Scale (HERRS) and examine its psychometric properties in elderly and adult individuals. Subject and methods: This study was conducted on 220 elderly and adult individuals (63.68±10.31 years old, 68.2% female, 31.8% male) living in their homes. The participants completed the Sociodemographic Information Form, Home Environment Conditions Evaluation Form for Falls, and Home and Environment Risk Rating Scale. In addition, psychometric measurement results for horizontal and vertical measurements were analyzed by exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) methods. Results: It was found that the Kaiser–Mayer–Olkin (KMO) value for horizontal and vertical measurements were 0.613 and 0.704, respectively. Results of EFA for horizontal and vertical measurements revealed that five factors together explain 72.033% and three factors together explain 68.368% of the total variance, respectively. The result of CFA for horizontal and vertical measurements demonstrate that the 5-sub-dimension horizontal scale structure and the 3-sub-dimension vertical measurement structure generally fit acceptable in this scale. Cronbach's alpha was satisfactory in all of the measurements (0.73 and 0.80 respectively); the ICCs were good/excellent in all of the measurements (0.99 and 0.90, respectively). Conclusion: The results show that HERRS has the potential to examine the risks of the home environment adequately for the home structure of Turkish society in detail and is a valid and reliable test that health professionals can use.